2020
DOI: 10.1088/1755-1315/457/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of chlorpyrifos and BPMC by the bacteria isolated from contaminated shallot farm soil

Abstract: Accumulation of insecticide residues is harmful to the environment and human living. The research was conducted to explore the chlorpyriphos and BPMC degrading bacteria from contaminated shallot farm soils and to formulate bacterial consortium to be applied as the insecticides bioremediation agent. Among nineteen bacterial isolates, K10 and K14 bacterial isolates could degrade up to 38.3% and 43.3% chlorpyrifos contained in its growth medium in 5 days, respectively. Two bacterial isolates namely B21 dan B17 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The prolonged exposure caused bacteria to develop ability to utilize the chemical as a source of carbon, as evidenced by the ability to grow in the media that contains CP as the only carbon source. Some previous studies have reported the degradation ability of Pseudomonas sp ., Bacillus sp ., and Alcaligenes faecalis against CP ( Farhan et al., 2012 ; Akhdiya et al., 2020 ; Ambreen and Yasmin, 2021 ), but there is no documented knowledge that links the other isolated species to biodegradation of organophosphates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prolonged exposure caused bacteria to develop ability to utilize the chemical as a source of carbon, as evidenced by the ability to grow in the media that contains CP as the only carbon source. Some previous studies have reported the degradation ability of Pseudomonas sp ., Bacillus sp ., and Alcaligenes faecalis against CP ( Farhan et al., 2012 ; Akhdiya et al., 2020 ; Ambreen and Yasmin, 2021 ), but there is no documented knowledge that links the other isolated species to biodegradation of organophosphates.…”
Section: Discussionmentioning
confidence: 99%
“…The findings show that all four isolates can use CP as the sole energy source, without requiring additional nutrients to induce expression of OP-degrading enzymes. The variations in the degradation performance of the isolated strains can be attributed to differences in microbial activity and degradation pathways ( Akhdiya et al., 2020 ; Ambreen and Yasmin, 2021 ). The current results are better compared to those reported in some earlier studies, especially concerning the time needed for maximum degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations